Pollution control in fertilizer production - Hodge, C.A; Popovici, Neculai N. (Environmental science and pollution control, 1994)
Addresses various aspects of pollution control for the mining, production, transportation, and distribution of chemical fertilizers covering technologies for various segments of the industry, including raw materials production, end products, and by-products.